(untitled) (Medical Forum Monthly, 2024)
Objectives: To determine the risk factors associated with development of diabetic foot ulcers Study Design: Descriptive / cross-sectional Place and Duration of Study: This study was conducted at the Department of Internal Medicine, Services Hospital, Lahore from 1st January 2017 to 31st July 2017. Materials and Methods: One hundred and fifty diabetics aged between 20-75 years presenting to surgical OPD / emergency with diabetic foot ulcers were enrolled. Patients with comorbidities like congestive cardiac failure, chronic renal failure and chronic liver disease were excluded from the study. The complete history was taken regarding duration of diabetes and its management. A detailed general physical examination was performed in each case along with sensory examination and ABI testing using Doppler ultrasound. Blood sample was sent for HbA1c to check for glycemic control. Ulcer debris was sent for culture and sensitivity. Results: There were 90 males and 60 females. Peripheral neuropathy was present in 53.3% patients, 64% had absent or diminished peripheral pulses, 46.7% had poor glycemic control. Underlying infection was seen in upto 90% of the patients. Footwear trauma was present in 40% of the cases. Thirty (20%) of the patients had to undergo amputation eventually while rest were managed conservatively. Conclusion: Prolonged diabetes, presence of underlying infection, peripheral vascular disease and peripheral neuropathy are the major risk factors responsible for development of diabetic foot ulcer. There is a dire need to educate diabetic regarding strict glycemic control and meticulous foot care.